Strategi Adaptasi Siswa pada Pembelajaran Sosiologi di SMA Negeri 8 Kupang - Timoteus Aman (PENSOS : Jurnal Penelitian dan Pengabdian Pendidikan Sosiologi, 2024)
The aim of this research is to determine students' adaptation strategies in participating in sociology learning at SMA Negeri 8 Kupang. The approach used in this research is qualitative. The research subjects using the purposive sampling technique consisted of school principals, teachers and students of SMA Negeri 8 Kupang. Research data was collected through interviews and documentation. This research data was analyzed using the interactive analysis technique of the Milles and Huberman model. This research found several findings. First, the adaptation strategies used by students at SMA Negeri 8 Kupang are quite good and varied. This can be seen from the adaptation strategies that have been carried out by students as well as assistance from the school, such as special guidance from teachers, providing supporting facilities such as books and the internet, and even going out into the community to carry out observations. Second, there are driving and inhibiting factors in the adaptation strategy process carried out by students in sociology learning at SMA Negeri 8 Kupang, driving factors such as motivation from teachers, providing supporting facilities such as books and the internet. Meanwhile, factors inhibiting students include skipping school, being lazy about doing assignments and lack of support from parents.